Helicobacter pylori an atlas of investigation and management - Holton, John (Clinical Pub., 2012)
Comprehensive illustrated guide to gastrointestinal disorders caused by H.pylori. Instructive sections presented in a clinical context cover: genomics, metabolism, taxonomy, epidemiology, pathogenesis, with detailed chapters on diagnosis and management of GI disease. Suitable for gastroenterologists, clinical microbiologists, general physician.